Student Literacy Capacity: Improving Literacy Skills Based on Teaching at the Right Level (TARL) - AR. HOMAINI; Pung Purwadi; Widya Hariska; Danang Aris Setyawan; Vebryani Surfi (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2025)
Teaching at The Right (TaRL) innovation is an innovative step where this strategy will be able to increase literacy rates and make it easier for teachers to teach structured and comprehensive learning materials so that success will be achieved in the learning process in the educational environment. The research method uses a descriptive qualitative method that is based on an inductive mindset, which is based on participatory objective observation of a social symptom (phenomenon), namely an approach or exploration to explore and understand a central symptom. The results of the study showed that the Teaching at the Right Level (TaRL) method was able to increase the literacy skills of students at the beginner level to 0 with a range of grades 3-6 of elementary school. In addition, this method is also effective in increasing the literacy capacity of students where the number of students at the story level was able to penetrate 56.87% from the previous 46.47%.